2018
DOI: 10.1108/jd-08-2017-0120
|View full text |Cite
|
Sign up to set email alerts
|

The heart of music classification: toward a model of classifying musical medium

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent repository linkThe heart of music classification: towards a model of classifying musical medium AbstractPurpose: This article seeks to understand the classification of musical medium, which is a critical part of music classification. It considers how musical medium is currently classified, provides a theoretical understanding of what is currently problematic, and proposes a model wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…Introduction to the medium facet Lee and Robinson (2018) show how medium -who is singing or playing the music -is actually a facet made up of different arrays, in sometimes complex sets of interrelationships. This section will focus on two areas of medium which appear to be particularly important to questions of orthogonality, as well as being primordial in the classification of medium.…”
Section: Orthogonality Between Medium and Form/genrementioning
confidence: 99%
See 3 more Smart Citations
“…Introduction to the medium facet Lee and Robinson (2018) show how medium -who is singing or playing the music -is actually a facet made up of different arrays, in sometimes complex sets of interrelationships. This section will focus on two areas of medium which appear to be particularly important to questions of orthogonality, as well as being primordial in the classification of medium.…”
Section: Orthogonality Between Medium and Form/genrementioning
confidence: 99%
“…This section will focus on two areas of medium that appear to be particularly important to questions of orthogonality, as well as being primordial in the classification of medium. Lee and Robinson (2018, p. 265–266) identified the categorization into vocal and instrumental music as the primary and most significant categorization within musical medium. Lee and Robinson (2018, p. 265) posited that medium foci generally live in either the vocal or instrumental sides of the medium facet.…”
Section: Orthogonality Between Medium and Form/genrementioning
confidence: 99%
See 2 more Smart Citations
“…To discuss discords further, an example from the medium facet is used: vocal/instrumental categorization. In a study of vocal/instrumental categorization, Lee and Robinson (, p. 266) found that 14 out of 19 classification schemes for music had a primary categorization into vocal and instrumental categories, with some categorization also seen in four out of five of the remaining schemes. Therefore, these bibliographic classifications show a strong adherence to dividing musical medium between vocal and instrumental.…”
Section: Discords: When Bibliographic and Scientific Classification Dmentioning
confidence: 99%